Muscle activation patterns in paralympic and novices hand cycling during incremental test - Kratzenstein, S.; Brückner, J. P. (Journal of Human Sport & Exercise, 2021)
The few studies on muscle timing in hand cycling are difficult to classify in the motor skill acquirement due to their variety of methods and content. This study aims to replicate two existing studies and thus to extend and connect the current state of research concerning the muscle timing during synchronous pedalling. The activity on- and offset of biceps brachii, triceps brachii, posterior deltoid, anterior deltoid, upper trapezius, and pectoralis major were identified during an incremental test of an elite and three novice athletes. The results showed differences in inter-muscular coordination between the elite and novice hand cyclists. Although the distinction between active and inactive phases was already evident in novice data, the activation pattern of the elite athlete showed an even more precise differentiation between these two phases. These time windows remained stable even with increasing load accompanied only by changes in all signal amplitude, except for deltoid activity, which showed a later onset and offset with increasing load. Thus, in training of hand cyclist novices, the muscle timing concerning the duration and the crank position should be considered. In future studies, the effect of handicap severity and crank frequency must be studied in greater detail.